The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1182/blood-2007-01-065714
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of VEGFR-1 and VEGFR-2 in the aberrant hematopoiesis associated with elevated levels of VEGF

Abstract: Vascular endothelial growth factor (VEGF), a major factor in tumor-host interactions, plays a critical role in the aberrant hematopoiesis observed in cancer-bearing hosts. To dissect the roles of VEGF receptor (VEGFR)-1 and VEGFR-2 in cancer-associated hematopoiesis in vivo, we selectively stimulated VEGFR-1 and VEGFR-2 by continuous infusion of receptor-specific ligands or selective blockade with VEGF receptor-specific antibodies in mice infused with recombinant VEGF at levels observed in tumor-bearing animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
175
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(180 citation statements)
references
References 51 publications
2
175
1
2
Order By: Relevance
“…24 In mouse model of chronic infusion of VEGF, VEGFR2 signaling significantly inhibited thymic T-cell development and decreased total number of splenic T cells, whereas VEGFR1 signaling contributed to the mobilization of T cells such as T precursors from the bone marrow and T cells from thymus to spleen. 38 Furthermore, the treatment of neutralizing anti-VEGFR1 Ab and exogenous VEGF did not affect the suppressive function of CD4 1 VEGFR1 high T cell. However, VEGFR1 would be involved in the migration of these cells and cause cleavage of IL-2 receptor a (CD25) from the surface of activated T cells through the induction of matrix metalloproteinases (MMPs) under a certain environment such as VEGF or a ligand-enriched environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In mouse model of chronic infusion of VEGF, VEGFR2 signaling significantly inhibited thymic T-cell development and decreased total number of splenic T cells, whereas VEGFR1 signaling contributed to the mobilization of T cells such as T precursors from the bone marrow and T cells from thymus to spleen. 38 Furthermore, the treatment of neutralizing anti-VEGFR1 Ab and exogenous VEGF did not affect the suppressive function of CD4 1 VEGFR1 high T cell. However, VEGFR1 would be involved in the migration of these cells and cause cleavage of IL-2 receptor a (CD25) from the surface of activated T cells through the induction of matrix metalloproteinases (MMPs) under a certain environment such as VEGF or a ligand-enriched environment.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and VEGFR have profound effects on both developmental hematopoiesis and pathologic conditions. [32][33][34][35][36][37][38] We first investigated the expression level of VEGFR1 in the murine thymocytes and T cells. We observed DN, DP, and SP (CD4 and CD8) thymocytes expressed VEGFR1.…”
Section: Discussionmentioning
confidence: 99%
“…5B). To validate this finding further, we treated F1 isografts of spontaneous MMTV-PyVT breast cancer with IgG or DC101 at different doses (10,20, and 40 mg/kg). Only quarter-dose DC101 treatment significantly increased tumorinfiltrating CD4 + and CD8 + T cells (Fig.…”
Section: Lower-dose Anti-vegfr2 Antibody Treatment Promotes T-cell Tumormentioning
confidence: 99%
“…Proangiogenic factors not only suppress the function of various immune cells (10) but also diminish leukocyte-endothelial interactions and hinder the infiltration of immune effector cells into the tumor parenchyma (11). Clinical studies consistently support the view that malignant tumors are nonpermissive to T effector cell accumulation (3,7,12).…”
mentioning
confidence: 99%
“…3,8,12 It has been suggested that different tumor-derived factors, such as granulocyte macrophage-colony-stimulating factor (GM-CSF), vascular endothelial growth factor (VEGF), IL-1␀, and prostaglandins, can mobilize MDSC recruitment from bone marrow hematopoietic precursors and induce the immunosuppressive phenotype. [13][14][15][16][17][18] While this immunosuppressive phenotype is a trademark of MDSCs, there is no clear consensus on their suppressive mechanism. Nevertheless, the L-arginine metabolism often seems to play a central role in the immune-suppressive activity of MDSCs.…”
Section: Introductionmentioning
confidence: 99%